Pengadaan Barang dan Jasa dalam Rangka Percepatan Penanganan Covid-19 - Triasti, Deby (Syntax Idea, 2021)
Emergency procedures are simple and different from direct appointment, the Budget User (PA) instructs the PPK to appoint providers to carry out work based on the PA's requirements for handling Covid-19. PA in the APBN is the minister or head of the institution while in the APBD structure, PA is the head of the region ie the governor or regent or mayor. Providers are used to providing the needs of the work unit concerned but must be ensured that there is no KKN, for example through mark ups, kickbacks, bribes or promises to provide other work in the future which is detrimental to the country's finances. Minister of Finance Sri Mulyani Indrawati said that the procurement of goods and services for emergencies such as now is already regulated in LKPP Institution Regulation No. 13 of 2018 concerning Procurement of Goods / Services in Handling Emergency Situations. Many changes in the State Budget (APBN) as well as the direct appointment mechanism for Personal Protective Equipment (PPE), masks and hand sanitizers can cause an atmosphere of concern. Even with direct appointment there are still a few things related to the committee and that is part of accountability, but Presidential Instruction No. 4 of 2020 is what the most important and Presidential Regulation regarding the procurement of goods / services is unnecessary, another legal basis is sufficient to deal with this unusual situation.